Ipsilateral femoral neck and intertrochanteric fractures with posterior dislocation of the hip: A report of two cases. (24th April 2020) - Su, Chenxian; Liu, Yangbo; Wu, Peng; Yuan, Jiandong; Lang, Junzhe; Wu, Congcong; Zhang, Yiou; Chen, Li; Chen, Lei
Traumatic hip dislocation usually occurs in young patients, with the increasing number of high-energy injuries, and 62–93% of reported adult traumatic hip dislocations were caused by high-speed motor vehicle crashes. However, ipsilateral femoral neck fractures and intertrochanteric fractures with posterior dislocation of the hip are extremely rare, and this injury poses a challenge to orthopaedic surgeons. Here, we report two cases of simultaneous ipsilateral femoral neck fracture, intertrochanteric fracture and posterior dislocation of the hip joint in young patients who were treated with proximal femoral locking compression plate (PFLCP). The long-term follow-up (one patient was followed up for 3 years and the other for 7 years) showed that these patients had excellent functional outcomes with near-normal ranges of hip movement. The authors believe that using smaller plates with the lateral PFLCP is an acceptable method to treat this injury in young patients.